LITERARY ANALYSIS OF IKROM OTAMURAD AND HIS WORKS - Oxbutayeva Dildora Zoirovna (Modern American Journals, 2025)
This article, the analysis of the famous Uzbek poet and writer Ikrom Otamurad, his life and work, works, poems and epics Analysis was illuminated and analyzed on the basis of various approaches.
Keywords: Poem, psyche, line, meaning, psychology, heart, polish, creativity, creativity.